2011
DOI: 10.1007/s10059-011-1043-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the miR399-PHO2 Module in the Regulation of Flowering Time in Response to Different Ambient Temperatures in Arabidopsis thaliana

Abstract: A moderate change in ambient temperature significantly affects plant physiology including flowering time. MiR399 and its target gene PHOSPHATE 2 (PHO2) are known to play a role in the maintenance of phosphate homeostasis. However, the regulation of flowering time by the miR399-PHO2 module has not been investigated. As we have previously identified miR399 as an ambient temperature-responsive miRNA, we further investigated whether a change in expression of the miR399-PHO2 module affects flowering time in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 36 publications
1
87
0
Order By: Relevance
“…Relative abundance of the transcripts was calculated by the statistical formula from geNorm (Vandesompele et al, 2002). For reference genes for quantification by RT-qPCR, two stably expressed genes [PP2AA3 (AT1G13320) and SAND family protein (AT2G28390)] were used to follow the 'The eleven golden rules for quantitative RT-PCR' (Kim et al, 2011;Udvardi et al, 2008). All RT-qPCR experiments were carried out in two or three biological replicates (independently harvested samples at different days) with three technical triplicates, each with similar results.…”
Section: Expression Analysesmentioning
confidence: 99%
“…Relative abundance of the transcripts was calculated by the statistical formula from geNorm (Vandesompele et al, 2002). For reference genes for quantification by RT-qPCR, two stably expressed genes [PP2AA3 (AT1G13320) and SAND family protein (AT2G28390)] were used to follow the 'The eleven golden rules for quantitative RT-PCR' (Kim et al, 2011;Udvardi et al, 2008). All RT-qPCR experiments were carried out in two or three biological replicates (independently harvested samples at different days) with three technical triplicates, each with similar results.…”
Section: Expression Analysesmentioning
confidence: 99%
“…In addition, SVP has been shown to act as a link in small RNA-mediated flowering in response to different ambient temperatures (Lee et al, 2010). It has also been reported that the microRNA399-PHOSPHATE2 module plays a role in the regulation of ambient temperature-responsive flowering (Kim et al, 2011).…”
mentioning
confidence: 99%
“…The miR156 and miR172 are two main factors that control the flowering time in the plant aging pathway (Huijser and Schmid, 2011;Yamaguchi and Abe, 2012;Wang, 2014). Other miRNA families including miR159, miR399, and OsmiR393 have also been shown to function in the control of flowering time (Achard et al, 2004;Kim et al, 2011;Xia et al, 2012). These miRNA-regulated pathways that control plant flowering time are themselves regulated by environmental factors, e.g.…”
mentioning
confidence: 99%